CRUSTAL STRUCTURE OF THE MAKAROV BASIN, ARCTIC OCEAN DETERMINED BY SEISMIC REFRACTION - Sorokin M.Yu.; Zamansky Yu.Ya.; Langinen A.Ye.; Jackson H.R.; Macnab R. (My University, 1999)
Wide-angle seismic reflection/refraction data, recorded on ten seismographs from five large explosive charges, clearly define the crustal and upper mantle velocities of the Makarov Basin. These data are combined with a tangential seismic reflection profile and with Russian navy refraction velocities to produce a seafloor to upper mantle velocity–depth function. The gently dipping sedimentary horizons contrast with the hummocky basement topography on the reflection profile. The seismic basement is interpreted as oceanic layer 2 consistent with the Russian navy velocities. Velocities of 6.7 km s−1 determined for the lower crust and 8.0 km s−1 for the upper mantle are constrained by the seismic record sections. The 6.7 km s−1 velocity layer is interpreted as oceanic crust layer 3. The well-resolved thickness of this layer of 15 km is substantially greater than the average thickness for layer 3 of 4 km. The velocities and thickness from the Makarov Basin, oceanic plateaus and hotspots, and continental crust are summarized for comparison. The character of seismic reflection basement and the velocity–depth function are consistent with thick oceanic crust in the Makarov Basin.